Agrobacterium tumefaciens–Mediated Transformation of Three Milkweed Species (Asclepias hallii, A. syriaca, and A. tuberosa: Apocynaceae). Issue 1 (9th March 2020) - Keen, Patricia; Hastings, Amy Picard; Agrawal, Anurag A.; Van Eck, Joyce
Abstract: Milkweeds have ecological significance for insect herbivores that rely on them as hosts for either part of or the entirety of their life cycles. Interesting interactions, some of which are not completely understood, have evolved over time. To develop these species as models to elucidate the interplay with insect herbivores, we established Agrobacterium tumefaciens –mediated transformation approaches for Asclepias hallii (Hall's milkweed), A . syriaca (common milkweed), and A . tuberosa (butterflyweed). The method is based on infection of stem internodal explants, which were more amenable to transformation than leaf explants. We found that addition of freshly prepared dithiothreitol was critical to prevent browning of stem explants. Depending on the species, the time from infection to the regeneration of transgenic lines ranges from 2 to 4 months. Transformation efficiency for A . hallii was 9%, whereas efficiencies for A . syriaca and A . tuberosa were 6% and 13%, respectively. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Agrobacterium tumefaciens –mediated transformation of Asclepias internodal stem explants Basic Protocol 2 : Preparation of Agrobacterium glycerol stocks containing gene constructs